Use of the fatigue severity scale to assess clinically reliable temporal changes in post-stroke fatigue by stroke type and subtype - Barker-Collo S; Krishnamurthi R; Feigin V; Nair B; Barber A; Thrift AG; Ranta A; Bennett D; Douwes J; Tautolo E-S; Cadilhac DA; Parag V; et al. (CSIRO Publishing, 2024)
BACKGROUND: A recent consensus statement on post-stroke fatigue noted the Fatigue Severity Scale (FSS) should be the primary outcome measure in post-stroke fatigue research. It also noted that data to calculate clinically reliable changes on the FSS have not been established for stroke. We present FSS data collected at 1 and 12 months post stroke, allowing the assessment of clinically reliable change by stroke type and subtype for ischaemic stroke (IS). METHODS: The sample included all participants of the fifth Auckland Region Community Outcomes of Stroke study (ARCOS-V) who consented and had FSS data (n = 338). Stroke type was recorded (IS, intracerebral haemorrhage (ICH), and subarachnoid haemorrhage (SAH)), and IS subtypes were defined using the Trial of Org 10172 in Acute Stroke Treatment (TOAST) classifications. 'Clinically reliable change' between 1 and 12 month FSS scores was calculated using Jacobsen and Traux's updated formula. RESULTS: Participants with ICH had the highest FSS scores at 1 month. Across IS subtypes, those with small vessel disease had the highest FSS scores at 1 month, and this increased at 12 months. Statistically significant reductions in mean FSS were found for patients with IS of other aetiology and SAH. Regarding clinically reliable changes, the greatest proportion of individuals had no clinically reliable change in FSS, up to 20% experienced reliable reductions, and 0-11% experienced reliable increases in FSS scores. CONCLUSION: Although most participants had no clinically reliable change in fatigue between 1 and 12 months, statistically significant reductions in FSS were identified for patients with IS and SAH. Of those who did experience reliable change, the majority had reductions in fatigue over time.
Keywords: clinically reliable change; cut-offs for reliable change; fatigue; ischaemic subtype; longitudinal; stroke; Humans; Fatigue; Male; Female; Severity of Illness Index; Aged; Middle Aged; Stroke; Subarachnoid Hemorrhage; Ischemic Stroke; Aged, 80 and over; Reproducibility of Results; Time Factors; Cerebral Hemorrhage